Some Weyl Modules for Simple Algebraic Groups of Type B4 and D4. Issue 9 (1st September 2016) - Wiggins, Elizabeth
Abstract : Let G be a simply connected, semisimple algebraic group of type B 4 or D 4 over an algebraically closed field of characteristic p > 0. We determine the characters of certain simple modules for these groups by calculating the composition factors of the Weyl modules.